Arginine requirement for egg production in Japanese quail - Callili, Daniel [UNESP]; Silva, Marlon Jocimar Rodrigues da [UNESP]; Sánchez, Camilo André Pereira Contreras [UNESP]; Basílio, Letícia Silva Pereira [UNESP]; Macedo, Bruno Marcos De Paula [UNESP]; Teixeira, Luiz Antonio Junqueira; Lima, Giuseppina Pace Pereira [UNESP]; Tecchio, Marco Antonio [UNESP] (Elsevier, 2022)
The objective of this study was to determine the ideal arginine intake for egg production in Japanese quail using the dilution technique. A completely random design was used, with 8 treatments (seven concentrations of arginine plus a control diet) and ten replicates, totaling 80 Japanese quails. The digestible arginine levels included in the study were 0.361%, 0.603%, 0.843%, 1.084%, 1.204%, 1.311%, and 1.460%. The variables analyzed were feed intake, egg production (EP), egg weight, egg output (EO), feed conversion ratio, and body weight were performed using a mixed model. When the effect of arginine levels (P ≤ 0.05) was detected, the model's broken line linear-plateau (BL), quadratic-plateau (BLq), and the first intercept of the BLq in the plateau of BL were adjusted to determine the ideal arginine intake. It observed that the arginine levels modified the quail responses (P < 0.001). Egg production was 10% with the 0.361% arginine in diet and recovered (97%) with the 1.311% arginine diet. The BL and BLq models estimated 232 mg/quail per day and 351 mg/quail per day for EO, respectively. The first intercept obtained was 290 mg/quail per day or 1,411%, which was considered the optimum level arginine intake for EO in Japanese quail.
Keywords: amino acid; broken line linear-quadratic-plateau; Coturnix coturnix japonica; egg production; requirement